2022
DOI: 10.3390/en15197016
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method of Deep Learning for Shear Velocity Prediction in a Tight Sandstone Reservoir

Abstract: Shear velocity is an important parameter in pre-stack seismic reservoir description. However, in the real study, the high cost of array acoustic logging leads to lacking a shear velocity curve. Thus, it is crucial to use conventional well-logging data to predict shear velocity. The shear velocity prediction methods mainly include empirical formulas and theoretical rock physics models. When using the empirical formula method, calibration should be performed to fit the local data, and its accuracy is low. When u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…While these empirical relations have proved to be very useful, especially considering the cost of obtaining direct measurements of shear velocity, they are very often unreliable and inaccurate. Furthermore, they are very lacking when it comes to generalization, where several relations need to be developed to account for the various (Jiang et al, 2022). While these relations may have inherent limitations and varying applicability across geological settings, they serve as efficient shortcuts in the absence of direct shear velocity measurements, aiding in the interpretation and understanding of subsurface structures and rock properties during exploration and development endeavors (Fabricio et al, 2015).…”
Section: Empirical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While these empirical relations have proved to be very useful, especially considering the cost of obtaining direct measurements of shear velocity, they are very often unreliable and inaccurate. Furthermore, they are very lacking when it comes to generalization, where several relations need to be developed to account for the various (Jiang et al, 2022). While these relations may have inherent limitations and varying applicability across geological settings, they serve as efficient shortcuts in the absence of direct shear velocity measurements, aiding in the interpretation and understanding of subsurface structures and rock properties during exploration and development endeavors (Fabricio et al, 2015).…”
Section: Empirical Methodsmentioning
confidence: 99%
“…Due to the potential improvement in the shear wave velocity prediction in complex reservoirs, data-driven models, analytical, rock physics and ML models have been used in several studies over the past two decades (Shawaf et al, 2022). One of the recent studies on slowness prediction using ML algorithms was conducted by (Jiang et al, 2022) who compared the shear wave velocity obtained from logging tools with the one obtained using empirical models. The authors then applied a novel method of deep learning (DL) to predict the shear wave velocity in a tight sandstone reservoir and found that the prediction accuracy is higher than the empirical equations (Zhang et al, 2020) tested theoretical, petrophysical, and machine learning models in a complex carbonate reservoir using conventional logs.…”
Section: Introductionmentioning
confidence: 99%
“…The validation of these correlations involves field investigations where both N SPT data and direct measurements of V s are collected at specific sites [122]. These data are used to test the accuracy of the correlations by comparing predicted V s values with measured V s values.…”
Section: S -N Spt Correlationsmentioning
confidence: 99%
“…In addition, the relationship between S-wave velocity and its influencing variables is often non-linear. This renders traditional empirical formulas inaccurate in real-world applications and unable to achieve the desired prediction accuracy of S-wave velocity even for full waveform inversion (Oh et al, 2018;Jiang et al, 2022;Rajabi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%